EVALUATION OF USE OF ANALGESICS IN PAIN MANAGEMENT AMONG SURGEONS IN A TERTIARY CARE HOSPITAL - Dawane, Jayshree; Khade, Kalyani; Ingale, Yamini; Pandit, Vijaya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to evaluate pain and to assess if analgesic prescriptions are according to the World Health Organization guidelines. Methods: The study was conducted in the Department of Surgery in a tertiary care hospital. Patients with age >18 years, of either sex, admitted to surgery ward were included in the study. Pain assessment was done using a visual analog scale and McGill questionnaire. Information obtained from case paper sheets was recorded, such as name of analgesics, the generic name of prescribed analgesics, dosage, route of administration, frequency, number of analgesics per prescription, and non-pharmacological techniques. Data generated from the questionnaire were entered into an Excel sheet, and percentages were calculated. Results: A total of eight different analgesics were prescribed in the study group. Paracetamol was the maximally prescribed drug (40%). In 48% of cases, antacids were given along with analgesics. A majority of analgesics were prescribed in generic names (52%). No drug was prescribed to almost 18% cases even though the pain intensity was of mild-to-moderate intensity. Conclusion: Commonly prescribed drugs were paracetamol + tramadol. Prescription pattern of analgesics is partially deviating from standard guidelines. Generic names were written in the majority of prescriptions, which is in accordance with standard prescription writing.